Using δ13C and δ18O to analyze loblolly pine (Pinus taeda L.) response to experimental drought and fertilization. (21st November 2019) - Lin, Wen; Domec, Jean-Christophe; Ward, Eric J; Marshall, John; King, John S; Laviner, Marshall A; Fox, Thomas R; West, Jason B; Sun, Ge; McNulty, Steve; Noormets, Asko
Abstract: Drought frequency and intensity are projected to increase throughout the southeastern USA, the natural range of loblolly pine ( Pinus taeda L.), and are expected to have major ecological and economic implications. We analyzed the carbon and oxygen isotopic compositions in tree ring cellulose of loblolly pine in a factorial drought ( 30% throughfall reduction) and fertilization experiment, supplemented with trunk sap flow, allometry and microclimate data. We then simulated leaf temperature and applied a multi-dimensional sensitivity analysis to interpret the changes in the oxygen isotope data. This analysis found that the observed changes in tree ring cellulose could only be accounted for by inferring a change in the isotopic composition of the source water, indicating that the drought treatment increased the uptake of stored moisture from earlier precipitation events. The drought treatment also increased intrinsic water-use efficiency, but had no effect on growth, indicating that photosynthesis remained relatively unaffected despite 19% decrease in canopy conductance. In contrast, fertilization increased growth, but had no effect on the isotopic composition of tree ring cellulose, indicating that the fertilizer gains in biomass were attributable to greater leaf area and not to changes in leaf-level gas exchange. The multi-dimensional sensitivity analysis explored model behavior under different scenarios, highlighting the importance of explicit consideration of leaf temperature in the oxygen isotope discrimination (Δ 18 Oc ) simulation and is expected to expand the inference space of the Δ 18 Oc models for plant ecophysiological studies.